Mengapa Audit Forensik Diperlukan: Expectation Gap dalam Konteks Pembuktian Kecurangan - Nadira Ramadhani; Rina Tjandrakirana DP (AKUNTANSI 45, 2026)
Ongoing fraud cases indicate that financial statement audits are not always able to detect and prove all fraudulent practices, leading to public criticism of the auditing profession and widening the audit expectation gap defined as the difference between the expectations of financial statement users and the responsibilities of auditors under auditing standards. This study aims to explain the necessity of forensic auditing in fraud investigation and its role in bridging the audit expectation gap arising from the inherent limitations of external audits. The study employs a Systematic Literature Review (SLR) by analyzing journal articles indexed in Scopus and SINTA published between 2020 and 2025 related to audit expectation gap, forensic auditing, and fraud. The findings indicate that the expectation gap is mainly driven by public misunderstanding of the scope of auditing and the inherent limitations of external audits, including risk-based approaches and sampling techniques. Forensic auditing, through its investigative approach, provides deeper evidence-gathering processes and serves as a complementary mechanism to reduce the expectation gap while enhancing transparency and accountability in auditing practices.